Analysis of a beta-lactam allergy assessment protocol challenging diverse reported allergies managed by an antimicrobial stewardship program - Max W. Jacobs; Derek N. Bremmer; Nathan R. Shively; Matthew A. Moffa; Tamara L. Trienski; Dustin R. Carr; Carley A. Buchanan; Thomas L. Walsh (Cambridge University Press, 2023)
Abstract Objective: To assess the safety and efficacy of a novel beta-lactam allergy assessment algorithm managed by an antimicrobial stewardship program (ASP) team. Design: Retrospective analysis. Setting: One quaternary referral teaching hospital and one tertiary care teaching hospital in a large western Pennsylvania health network. Patients or participants: Patients who received a beta-lactam challenge dose under the beta-lactam allergy assessment algorithm. Interventions: A beta-lactam allergy assessment protocol was designed and implemented by an ASP team. The protocol risk stratified patients' reported allergies to identify patients appropriate for a challenge with a beta-lactam antibiotic. This retrospective analysis assessed the safety and efficacy of this protocol among patients receiving a challenge dose from November 2017 to July 2021. Results: Over a 45-month period, 119 total patients with either penicillin or cephalosporin allergies entered the protocol. Following a challenge dose, 106 (89.1%) patients were treated with a beta-lactam. Eleven patients had adverse reactions to a challenge dose, one of which required escalation of care to the intensive care unit. Of the patients with an unknown or low-risk reported allergy, 7/66 (10.6%) had an observed adverse reaction compared to 3/42 (7.1%) who had an observed reaction with a reported high-risk or anaphylactic allergy. Conclusions: Our implemented protocol was safe and effective, with over 90% of patients tolerating the challenge without incident and many going on to receive indicated beta-lactam therapy. This protocol may serve as a framework for other inpatient ASP teams to implement a low-barrier allergy assessment led by ASP teams.